Irving Howe : a Life of Passionate Dissent. - Sorin, Gerald (NYU Press, 2003)
A New York Times "Books for Summer Reading" selection. Winner of the 2003 National Jewish Book Award for History. By the time he died in 1993 at the age of 73, Irving Howe was one of the twentieth century's most important public thinkers. Deeply passionate, committed to social reform and secular Jewishness, ardently devoted to fiction and poetry, in love with baseball, music, and ballet, Howe wrote with such eloquence and lived with such conviction that his extraordinary work is now part of the canon of American social thought. In the first comprehensive biography of Howe's life, historian Ger.